(untitled) (Malaysian Journal of Learning and Instruction, 2020)
Purpose - Internationalization of education has made it important to have not only a command of English as a global language, but also of Languages Other Than English (LOTEs), which can be a second, national or heritage language. This narrative inquiry explored LOTE teachers’ perspectives on their use of English and other pedagogical practices for teaching LOTE to international students. Methodology - Narratives of three language teachers from different linguistic and cultural backgrounds, teaching French, Korean and Mandarin at a private university in Malaysia were recorded. Their discussion addressed key issues in teaching LOTE such as teaching strategies, use of technology and the importance of using English for teaching LOTEs. Data was analysed using Nvivo, applying Saldana’s (2016) coding technique, consisting of structural, descriptive and values coding. 48 codes emerged during the first cycle coding, which were placed under nine categories in the second and final coding process. Findings - Data revealed that for achieving practical outcomes, technologically integrated teaching is an alternative to traditional teaching practices. Further, teachers’ narratives also showed the importance of English in LOTE teaching, owing to the internationalization of education. Significance – The study explored LOTE pedagogy through the narratives of teachers, who are key stakeholders. The findings will help LOTE teachers reflect on their own teaching practices, and familiarize them with current pedagogy, including technology integration. They would also be useful in other contexts where LOTE is offered as a foreign language.